Supporter or obstructer; experiences from contact person activities among Swedish women with breast cancer - Nilbert Mef; Carlsson Christina; Nilsson Kerstin (BMC, 2005)
Abstract Background Swedish patient associations for breast cancer patients (PABCPs) offer patients with breast cancer unlimited meetings with a breast cancer survivor, a contact person (CP). We applied the voluntary action perspective in this interview study with members of Swedish PABCPs in order to explore how women with breast cancer experienced their contact with a CP from a PABCP. Methods Audio-taped narratives from 8 women were analysed using Reissman's monitoring and Gee's analysis structure. Results Three themes appeared: 1. Shared experiences give new perspectives on having cancer, 2. Feelings of isolation are a part of the identity of the illness and 3. Relations with others enable self-help. However, the relationship with the CP is sensitive to timing, correct information and understanding. Conclusions CPs act as sounding boards and should optimally have capacity for listening, gives support and act as partner in this conversation. On the other hand, CPs should be aware that their presence and limited general medical knowledge could at times disturb the patient's psychological recovery and strengthen feelings of isolation. Thus, PABCPs must be careful in selecting CPs and offer relevant educational activities related to the themes identified herein.